The Roles of Cdk5-Mediated Subcellular Localization of FOXO1 in Neuronal Death - Zhou, Jiechao (J Neurosci, 2015)
Deficiency of cyclin-dependent kinase 5 (Cdk5) has been linked to the death of postmitotic cortical neurons during brain development. We now report that, in mouse cortical neurons, Cdk5 is capable of phosphorylating the transcription factor FOXO1 at Ser249 in vitro and in vivo. Cellular stresses resulting from extracellular stimulation by H(2)O(2) or β-amyloid promote hyperactivation of Cdk5, FOXO1 nuclear export and inhibition of its downstream transcriptional activity. In contrast, a loss of Cdk5 leads to FOXO1 translocation into the nucleus: a shift due to decreased AKT activity but independent of S249 phosphorylation. Nuclear FOXO1 upregulates transcription of the proapoptotic gene, BIM, leading to neuronal death, which can be rescued when endogenous FOXO1 was replaced by the cytoplasmically localized form of FOXO1, FOXO1-S249D. Cytoplasmic, but not nuclear, Cdk5 attenuates neuronal death by inhibiting FOXO1 transcriptional activity and BIM expression. Together, our findings suggest that Cdk5 plays a novel and unexpected role in the degeneration of postmitotic neurons through modulation of the cellular location of FOXO1, which constitutes an alternative pathway through which Cdk5 deficiency leads to neuronal death.